Postoje občanů a komunikace ve veřejné správě - Brychtová, Šárka; Duplinský, Josef (Univerzita Pardubice, 2002)
Primary way out for research analyses of positions of inhabitans and communication in public administration proving first understanding just positions, needs and interests of residents. Just finding from these researches can become way out for the successful communication of a institution with community. Sense of the article is just empirical study of positions of inhabitants to working of the public administration and typical negative phenomena in communication their representatives with public.
Keywords: komunikace s veřejností; občané; pracovníci; veřejná správa